Analysis Of Factors Related to Conscious Breast Self-Examination (BSE) Behavior in Women Of Childbearing Age (WCA) - Firzia, Zahra; Dinengsih, Sri; Lail, Nurul Husnul (Jurnal MIDPRO, 2022)
A survey of WUS aged 20-45 years in the Harapan Baru area of Bekasi City which was conducted randomly found 4 out of 10 WCA did not know the early detection of breast cancer and did not do BSE as a form of early detection of breast cancer. The purpose of this study is to analyze factors related to BSE behavior in WCA in the Harapan Baru area of Bekasi City in 2022. This research is a cross-sectional quantitative analytic type of research. The research sample amounted to 100 respondents with data collection using a questionnaire sheet. Data analysis through univariate and bivariate analysis using Chi-Square test. The results showed that BSE behavior in WCA 34.00% had knowledge of 32.00% with a higher education background of 62.00%, and obtained 43.00% of information sources, but there was still anxiety 58.00% despite the support of health workers 46 ,00%. There is a relationship between knowledge and BSE behavior (Ï-value 0.021), there is a relationship between education and BSE behavior (Ï-value 0.027), there is a relationship between information sources and BSE behavior (Ï-value 0.022), there is a relationship between anxiety and BSE behavior (Ï-value 0.014), there is a relationship between the support of health workers with BSE behavior (Ï-value 0.034).